English -learning mobile app designing for engineering students’ cross-disciplinary learning and collaboration - Tai, Yaming; Ting, Yu-Liang (Australasian Journal of Educational Technology, 2020)
Engineers must be able to collaborate with experts across disciplinary boundaries to successfully address the complex challenges of a contemporary workplace. The related training and research on motivating and engaging engineering students in schools is limited and rarely accounts for students’ lived experiences in the curriculum design. Meanwhile, programming is a medium of communication that can be reflexive with other domains and has been treated as a way of thinking about and exploring disciplines beyond computer science. In this study, engineering students used authoring tools of mobile app to design an English-learning app, in which English teachers provide feedbacks for revision, and a preliminary cross-disciplinary collaboration is asserted. The learning design referred to the frameworks of constructing socio-technical creativity to aid the students in employing their existing English knowledge to design mobile apps. The evaluation was conducted on the basis of the students’ designed apps and presentation, teachers’ feedback, and students’ self-reports. The results indicated that the common use of mobile apps in people daily life seemed to create a boundary object for the engineering students and English teachers to express, communicate, and coordinate their perspectives and knowledge. Students could view the engineering work from different aspects and appreciate English teachers’ comments and value their expertise. By accounting for the interests of students and schools’ limited resources, this study serves as a reference for cross-disciplinary learning and collaboration methodology.